Lanthanum induced lattice strain improves hydrogen sulfide capacities of copper oxide adsorbents. Issue 12 (21st October 2021) - Canning, Griffin A.; Azzam, Sara A.; Hoffman, Adam S.; Boubnov, Alexey; Alshafei, Faisal H.; Ghosh, Richa; Ko, Brian; Datye, Abhaya; Bare, Simon R.; Simonetti, Dante A.
Abstract: This work probes the effects of La on reactions involving CuO sorbents and H2 S in gaseous streams. La‐CuO sorbents with nominal La/Cu atomic ratios of 1:2 achieved higher capacities (27 and 36 g H2 S per 100 g sorbent) compared to CuO sorbents (25 g H2 S per 100 g sorbent). Comparison of the La‐CuO sorbents using energy dispersive x‐ray spectroscopy and La L3 ‐edge XAS suggested that increased capacity resulted from more uniform dispersion of La within the CuO phase (3.3 wt.% vs. 1.0 wt.% La). X‐Ray absorption near edge structure analysis suggested more electron‐rich Cu species in La‐CuO samples, while extended X‐ray absorption fine structure modeling showed an increase in single‐scattering path lengths for neighboring and near‐neighbor atoms. These changes suggest that La induces strain in the Cu‐O lattice, thereby increasing H2 S capacity by reducing energy barriers associated with surface reactions between oxygen atoms and adsorbed H2 S molecules.